PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN KOTO BARU MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING - Sudirman, Sudirman; Baviga, Rio (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This research aims to find out: 1) The extent of the influence of organizational culture on performance. 2) The extent of the influence of organizational commitment on performance. 3) The extent of the influence of organizational culture on OCB. 4) The extent of the influence of organizational commitment on OCB. 5) The extent of the influence of OCB on performance. 6) The extent of influence of organizational culture and organizational commitment on performance with OCB as an intervening variable. The population in this study was village officials in Koto Baru District with a total of 50 people. Next, the entire population was sampled as 50 people using a saturated sampling technique. The data analysis tool used is path analysis. Based on the research results, it shows that Organizational Culture has a significant effect on the Performance of Village Officials in Koto Baru District (tcount > ttable or (11.190 > 2.01290) and sig < ? (0.000 < 0.05)). Organizational Commitment has a significant effect on the Performance of Village Officials in Koto Baru District (tcount > ttable or (4.432 > 2.01290) and sig < ? (0.000 < 0.05)). Organizational culture has a significant effect on OCB in Village Officials in Koto Baru District (tcount > ttable or (4.794 > 2.01174) and sig < ? (0.000 < 0.05)). Organizational Commitment has a significant effect on OCB in Village Officials in Koto Baru District (tcount > ttable or (3.190 > 2.01174) and sig < ? (0.003 < 0.05)). OCB has a significant effect on the performance of village officials in Koto Baru District (tcount > ttable or (13.325 > 2.01290) and sig < ? (0.000 < 0.05)). Organizational culture on performance directly is 26.5%, while the influence of organizational culture through OCB on performance indirectly is 18.1%. Organizational Commitment on performance directly is 3.3%, while the influence of Organizational Commitment through OCB on performance indirectly is 4.3%.